PENERAPAN ALAT KENDALI KIPAS ANGIN MENGGUNAKAN MICROCONTROLLER ARDUINO MEGA 2560 DAN SENSOR DHT22 BERBASIS ANDROID - Ordila, Rian; Yulanda; Putra; Irawan, Yuda (Riau Journal Of Computer Science, 2020)
The control of the fan in the classrooms of the Ekatama Tourism Pekanbaru SMKS still uses a rope as a speed controller or manual. To simplify the control of fans in the classroom, a Fan Control Device Using an Arduino Mega 2560 Microcontroller and an Android-Based DHT22 Sensor. The whole tool is divided into several parts which consist of Smartphone, Arduio Mega 2560 Microcontroller, DHT22 Sensor, Bluetooth HC-06, 4ch Relay Module, LCD 1602, 1K Resistor, XL4005 Step Down, Power Supply 12V 3A, LED Diffused, Push Button, and DC fan. This tool works when a Bluetooth Smartphone connects to Bluetooth HC-06, from Bluetooth HC-06 then to a microcontroller to process commands, from a microcontroller then to a Relay module that works as a substitute for a switch that functions to activate and deactivate the fan according to the desired speed. The application of this tool can also work with manual or automatic functions. The results showed that applications on Smartphones can communicate with Arduino Mega 2560 with a distance of 25 meters if there is no barrier, and 15 meters if there is a barrier.